Amorphous cobalt sulfide electrode and its application in sulfide ion oxidation-assisted hydrogen production

Through the amorphous cobalt sulfide electrode and an acid-base asymmetric electrolyte system, combined with sulfur ion oxidation to assist hydrogen production, the problem of low oxygen evolution reaction efficiency in hydrogen production in water electrolysis is solved, and the production of high-efficiency hydrogen and sulfur is achieved, which reduces the production of The hydrogen potential has promoted the development of hydrogen energy.

CN115652323BActive Publication Date: 2025-01-03CHENGDU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211131779.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-01-03
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

The low efficiency of the anode oxygen evolution reaction in the existing water electrolysis hydrogen production technology leads to low overall energy conversion efficiency, limiting large-scale commercial applications.

Method used

Amorphous cobalt sulfide electrode is formed through hydrothermal reaction and electrochemical activation, combined with an acid-base asymmetric electrolyte system, and sulfur ion oxidation assists in hydrogen production, achieving efficient hydrogen and sulfur production.

Benefits of technology

It significantly reduces the hydrogen production potential, improves the energy conversion efficiency, realizes the production of zero energy consumption and hydrogen production and sulfur, and promotes the rapid development of hydrogen energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115652323B_ABST
    Figure CN115652323B_ABST
Patent Text Reader

Abstract

The present invention discloses an amorphous cobalt sulfide electrode and its application in sulfide ion oxidation-assisted hydrogen production. The amorphous cobalt sulfide electrode is prepared by the following method: (1) dissolving Co(NO)3 and CO·(NH)2 in water, immersing nickel foam NF in the solution, and performing a hydrothermal reaction to obtain nickel foam Co‑C / NF loaded with basic cobalt carbonate; (2) using the nickel foam Co‑C / NF loaded with basic cobalt carbonate as a working electrode, constructing a three-electrode system, performing a constant potential activation treatment in an electrolyte solution including NaOH and Na2S, and obtaining an amorphous cobalt sulfide Co‑S / NF electrode after electrochemical activation; when the Co‑S / NF is assembled as a cathode catalytic electrode in an asymmetric acid-base coupled electrolysis system, the energy consumption of hydrogen production is significantly reduced, and additional electricity can be generated in the hydrogen production process for sulfur production; this work provides unique insights into the in-situ transfer process of cobalt-based materials in the SOR catalytic process and the influence of asymmetric acid-base coupled electrolytes on electrochemical hydrogen production, and provides an important driving force for further research on large-scale and cheap hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of composite materials for electrocatalytic hydrogen evolution, and in particular to an amorphous cobalt sulfide electrode and application thereof in sulfide ion oxidation-assisted hydrogen production. Background Art

[0002] The rapid development of green and renewable clean energy has become a key solution to alleviate challenges such as the increasingly serious environmental pollution caused by the excessive use of traditional fossil fuels. Hydrogen is considered to be one of the best alternatives to fossil energy in the future due to its high energy density, zero carbon emissions and renewability. At the same time, water electrolysis can be powered by renewable electricity generated by clean energy such as solar and wind power, providing a green and sustainable way to produce hydrogen. However, the overall water splitting reaction (OWSR) is slow and has low energy conversion efficiency, which limits large-scale commercial applications. The low energy conversion efficiency of OWSR is mainly limited by the anodic oxygen evolution reaction (OER, 1.23V vs.RHE), which involves complex multi-proton coupled electron transfer processes and slow kinetics. Although many efficient OER catalysts have been designed, the theoretical thermodynamic difficulties predetermine the inevitable high voltage (much higher than 1.23V), low energy exchange efficiency and high energy consumption of OWSR to produce H2.

[0003] To fundamentally overcome this obstacle, an effective strategy is to utilize electrochemical oxidation reactions with lower theoretical oxidation potentials to replace the anodic OER, such as the electrochemical oxidation of alcohols, aldehydes, urea, and sulfur anions. In particular, the sulfide oxidation reaction (SOR: SOR) with ultra-low theoretical potentials 2-→S+2e-, E0=-0.48V vs.RHE) can not only significantly reduce power consumption, but also obtain high value-added negative electrode products (S8). In addition, since sulfur ions are typical harmful byproducts in industrial production, electrochemical SOR is also a green method to recover sulfur ions without introducing additional oxidants. Therefore, the coupling of anode SOR and cathode HER will make electrochemical hydrogen production more economically feasible while obtaining additional pollution control advantages. For the above-mentioned coupled system, the key to improving energy conversion efficiency is a highly active SOR catalyst. Some studies have shown that cobalt-based materials are effective catalysts for SOR. However, the relevant internal catalytic mechanism still needs further study, which is the basis for the targeted design of highly active SOR catalysts. During the electrocatalytic reaction, the catalytic material usually undergoes an in situ surface conversion process and forms effective active sites. In particular, the amorphous active materials formed in situ usually exhibit better catalytic performance than the initial crystalline materials due to the presence of a large number of defects and unsaturated sites. In-depth study of the dynamic process of electrode materials is crucial to understanding the catalytic mechanism and designing highly active and stable SOR catalysts. In addition to the catalyst, the electrolyte also has an important influence on the reaction voltage and energy consumption. It is worth noting that acidic solutions rich in hydrogen ions are favorable for HER, while SOR is more likely to occur in alkaline media. In addition, the acid-base coupling system has a huge potential difference, which will further promote hydrogen production at ultra-low potential. Therefore, acid-base asymmetric electrolytes also have the potential to significantly improve energy conversion efficiency. However, corresponding studies, including in situ dynamic conversion of catalytic materials and acid-base asymmetric electrolytes for SOR, have rarely been explored. Summary of the invention

[0004] The present invention provides an amorphous cobalt sulfide electrode and its application in sulfide ion oxidation-assisted hydrogen production, which solves the problems of high hydrogen evolution potential and low energy conversion efficiency in the prior art.

[0005] In order to solve this technical problem, the present invention provides the following technical solution:

[0006] An amorphous cobalt sulfide electrode, wherein the amorphous cobalt sulfide electrode is prepared by the following method:

[0007] (1) Dissolving Co(NO)3 and CO·(NH)2 in water, immersing nickel foam NF in the solution, and performing a hydrothermal reaction to obtain nickel foam Co-C / NF loaded with basic cobalt carbonate;

[0008] (2) A three-electrode system was constructed using nickel foam Co-C / NF loaded with basic cobalt carbonate as the working electrode. Constant potential activation treatment was carried out in an electrolyte solution including NaOH and Na2S to obtain an amorphous cobalt sulfide Co-S / NF electrode after electrochemical activation.

[0009] The concentration of Co(NO)3 in step (1) is 0.125 mol L -1 The concentration of CO·(NH)2 is 0.625 mol L -1 .

[0010] The hydrothermal reaction temperature is 100-140°C, and the hydrothermal reaction time is 6-10h.

[0011] The concentration of NaOH in step (2) is 1 mol L -1 , the concentration of Na2S is 1 mol L -1 .

[0012] The counter electrode of the three-electrode system is a graphite electrode, and the reference electrode is a Hg / HgO electrode or an Ag / AgCl saturated potassium chloride electrode.

[0013] The potential of the constant potential activation treatment is 0.35 V vs. RHE, and the activation treatment time is 10-12 h.

[0014] This scheme also provides the application of the above-mentioned amorphous cobalt sulfide electrode in sulfide ion oxidation-assisted hydrogen production, using H2SO4 solution as cathode electrolyte, NaOH and Na2S electrolyte solution as anode electrolyte, using a cation exchange membrane to separate the anode electrolyte and the cathode electrolyte to establish an asymmetric acid-base coupling electrolytic cell, and an anode catalytic electrode and a cathode catalytic electrode are respectively provided in the anode electrolyte and the cathode electrolyte, and the anode catalytic electrode uses the above-mentioned amorphous cobalt sulfide electrode.

[0015] Preferably, the cathode catalytic electrode uses a platinum carbon electrode, and the preparation method of the platinum carbon electrode is: 4 mg Pt / C powder (Pt mass fraction is 20%) is evenly dispersed in a mixture of 375 μL deionized water, 125 μL methanol and 20 μL Nafion; then the ink is evenly applied on carbon paper, and then the electrode is dried at 80°C for 12 hours. The obtained electrode is recorded as Pt-C / CP.

[0016] Preferably, the concentration of H2SO4 is 0.5 mol L -1 The concentration of NaOH electrolyte solution is 1 mol L -1 The concentration of Na2S electrolyte solution is 1 mol L -1 .

[0017] Preferably, the cation exchange membrane is a polyethylene cation exchange membrane.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] In this work, basic cobalt carbonate nanorod arrays (Co-C / NF) were synthesized on nickel foam (Co-C / NF) as a precursor electrocatalyst for SOR in alkaline media. Although Co-C / NF itself is inactive for SOR, the amorphous cobalt sulfide material (Co-S / NF) formed in situ on the surface of cobalt hydroxide carbonate during the SOR process shows effective activity for SOR. The Co-S / NF electrode only requires ultra-low potentials of 0.264 and 0.366 V vs. RHE to obtain 10 and 100 mA cm-2, respectively. -2 The current density is superior to other catalysts. The in-situ conversion of the highly crystalline basic cobalt carbonate surface into amorphous cobalt sulfide material is the key to improving the catalytic activity of SOR. Detailed studies on the composition and morphology changes of Co-C / NF show that basic cobalt carbonate can be in-situ transformed into amorphous cobalt-based sulfide-coated cobalt hydroxide carbonate needle nanorod arrays during the SOR process. At the same time, the amorphous cobalt-based sulfide formed on the surface in situ is highly amorphous.

[0020] The excellent Co-S / NF electrode was further applied to a unique asymmetric acid (0.5 M H2SO4, Pt-C / CP as catalytic electrode)-base (1 M NaOH and 1 M Na2S, Co-S / NF as catalytic electrode) coupled electrolyzer to achieve the production of hydrogen and sulfur while generating additional electricity with a peak power density of 50 mW cm -2 The cleverly designed acid-base asymmetric electrolyte system achieves zero-energy production of hydrogen and sulfur. This work provides detailed evidence for the dynamic in-situ changes of catalytic materials during the SOR process and the influence of the asymmetric electrolyte system, providing more possibilities for the design of efficient SOR catalysts and energy-saving electrolysis systems; at the same time, it provides new ideas for designing unique hydrogen production devices to obtain high energy exchange efficiency, thereby promoting the rapid development of hydrogen energy. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0022] Figure 1 Schematic diagram of the preparation process of Co-C / NF and Co-S / NF in Example 1 of the present invention, the corresponding in-situ surface activation process in the SOR process, and the XRD diagram.

[0023] Figure 2 These are material characterization diagrams of Example 1 of the present invention; wherein, (a) SEM image of Co-S / NF; (b) TEM image of Co-S / NF; (c) SEM image of Co-S / NF; (d) TEM image of Co-S / NF; (e) Co2p of Co-S / NF; and (f) S2p spectrum.

[0024] Figure 3 The electrochemical performance diagram of Example 1 of the present invention; wherein (a) polarization curve; (b) Tafel curve corresponding to the catalytic electrode; (c) Tafel slope and 10 mA cm -2 Comparison of potentials with respect to current density; (d) polarization curves normalized to the electrochemically active surface area; (e) corresponding Tafel curves of the catalytic electrode; (f) stability test of Co-S / NF on SOR.

[0025] Figure 4 The test graph of Example 1 of the present invention; (a) the polarization curve of Co-S / NF in 1M KOH with and without 1M Na2S; (b) the polarization curve of Co-S / NF in 1M KOH with and without 1M Na2S; (c) the polarization curve of Co-S / NF in 1M KOH with and without 1M Na2S; (d) the polarization curve of Co-S / NF in 1M KOH with and without 1M Na2S -2 Comparison of the potential of Co-S / NF in 1M KOH with and without 1M Na2S at a current density of 100 mA cm -2 (a) UV-visible spectra of the electrolyte samples corresponding to different reaction times (picture of the corresponding electrolyte is in the inset); (d) XRD characterization of the product S and standard sulfur.

[0026] Figure 5 Test diagrams of Examples 1, 3-4 of the present invention; wherein, (a) polarization curves of corresponding catalytic reactions based on RHE (including SOR and OER catalyzed by Co-S / NF (pH = 14) and HER catalyzed by Pt-C / CP (pH = 14), taking the absolute value of current density); (b) Pourbaix diagrams of SOR, HER and OER based on ordinary hydrogen electrode (NHE) under full pH conditions; (c) polarization curves of corresponding catalytic reactions based on NHE (including SOR and OER catalyzed by Co-S / NF (pH = 14) and HER catalyzed by Pt-C / CP (pH = 14), taking the absolute value of current density); (d) two-electrode polarization curves of different electrolyte combinations; (e) the dual-electrode system in the asymmetric acid (HER of Pt-C / CP)-base (SOR of Co-S / NF) coupled electrolyzer reaches 100 mA cm -2 (f) Faraday efficiency of hydrogen production; (g) Stability test of the two-electrode system in the asymmetric acid (HER of Pt-C / CP)-base (SOR of Co-S / NF) coupling system, schematic diagram of the electrolyzer (inset). DETAILED DESCRIPTION

[0027] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0028] Materials and reagents:

[0029] Cobalt nitrate hexahydrate (Co(NO)3·6H2O, AR) and urea (CO·(NH)2, AR) were purchased from Chengdu Cologne Chemical Co., Ltd.; sodium sulfide (Na2S, AR) and sodium hydroxide (NaOH, AR) were purchased from Chengdu Jinshan Chemical Co., Ltd.; nickel foam (NF) was provided by Kunshan Guangjiayuan New Materials Co., Ltd.; Pt / C (20%) was purchased from Alfa Aesar Chemical Co., Ltd.

[0030] Example 1

[0031] Preparation of Co-C / NF:

[0032] like Figure 1 As shown, nickel foam was first treated with 1 mol L -1 HCl was ultrasonically treated for 15 min, and then washed several times with distilled water and ethanol to remove surface impurities; Co(NO)3 (5 mmol) and CO·(NH)2 (25 mmol) were dissolved in 40 mL of deionized water under stirring. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave (50 mL), and the NF was vertically immersed in the solution and heated at 120 °C for 6 h. After naturally cooling to room temperature, the electrode was washed several times with deionized water and dried in an oven at 70 °C for 6 h to obtain nickel foam loaded with basic cobalt carbonate (Co-C / NF), with a mass loading of basic cobalt carbonate of approximately 2.3 mg cm -2 .

[0033] Preparation of Co-S / NF:

[0034] In the three-electrode system, the Co-C / NF electrode and graphite rod prepared in Example 1 were used as the working electrode and counter electrode, respectively, and the Hg / HgO electrode was used as the reference electrode. -1 NaOH and 1 mol L -1 The electrode was treated in a Na2S electrolyte at a constant potential of 0.35 V vs. RHE for 12 hours, and the electrode obtained after electrochemical activation was repeatedly washed with deionized water and dried to obtain a Co-S / NF electrode.

[0035] The obtained materials were used to characterize the microstructure and elements of the samples using a scanning electron microscope (SEM). X-ray diffraction (XRD) patterns were used to characterize the crystal structure and composition of the catalytic materials. Elemental composition analysis was performed using an X-ray photoelectron spectrometer (XPS). Electrochemical tests were performed on an electrochemical workstation. A three-electrode system was established with Co-S / NF catalytic electrode as the working electrode, graphite rod as the counter electrode, and Hg / HgO (alkaline electrolyte) and Ag / AgCl (acidic electrolyte) as reference electrodes. In a solution containing 1 mol L -1 1 mol L of Na2S -1 In NaOH electrolyte, at 0.01 V s -1 Linear sweep voltammetry (LSV) was performed at a scan rate of 1.0 50 40 45 50 40 ...

[0036] E RHE =E+E NHE +0.0591×pH……(1)

[0037] Where E RHE , E and E NHE They are the potential relative to RHE, the measured potential and the relationship between the potential and the point relative to the normal hydrogen electrode (NHE), respectively.

[0038] Example 2

[0039] Synthesis of Pt-C / CP

[0040] The preparation method of the platinum carbon electrode is as follows: 4 mg of Pt / C powder (Pt mass fraction is 20%) is uniformly dispersed in a mixture of 375 μL of deionized water, 125 μL of methanol and 20 μL of Nafion; then the ink is evenly coated on carbon paper, and then the electrode is dried at 80° C. for 12 hours. The obtained electrode is recorded as Pt-C / CP.

[0041] Example 3

[0042] An asymmetric acid-base coupled electrolyzer was established with 0.5 M H2SO4 as the cathode liquid (Pt-C / CP as the catalytic electrode), 1.0 M NaOH and 1.0 M Na2S as the anode liquid (Co-S / NF as the catalytic electrode) to test the HER, SOR and OER performances.

[0043] Example 4

[0044] The HER, SOR, and OER performances were tested in a symmetric alkaline electrolyzer using 1.0 M NaOH as the cathode liquid (Pt-C / CP as the catalytic electrode) and 1.0 M NaOH and 1.0 M Na2S as the anode liquid (Co-S / NF as the catalytic electrode).

[0045] Figure 1 The fabrication process of Co-S / NF is shown, which is in situ converted from basic cobalt carbonate needle-like nanorod arrays during the SOR process. The precursor catalyst of Co-C / NF is obtained by a simple hydrothermal route. According to the X-ray diffraction (XRD) pattern of Co-C / NF ( Figure 1 The three characteristic diffraction peaks at 44.5°, 51.8°, and 76.4° correspond to the nickel foam (NF) substrate (PDF#04-0850), and the other relatively weak characteristic peaks are attributed to Co(CO3) 0.5 (OH)·0.11H2O (PDF#48-0083). Scanning electron microscope (SEM) image of Co-C / NF ( Figure 2 a) shows that the entire surface of NF is covered by vertically grown needle-like nanorods. In addition, Figure 2 The transmission electron microscopy (TEM) image in b further confirms the formation of needle-like nanorods, and the clear lattice fringes with a width of 0.51 nm are given to Co(CO3) 0.5 The (020) lattice plane of (OH)·0.11H2O is consistent with the XRD pattern results. These findings indicate that the basic cobalt carbonate needle-shaped nanorod arrays were successfully prepared, which can fully expose their surface to the electrolyte and promote further surface in situ transformation.

[0046] Although Co-C / NF itself exhibits low intrinsic catalytic activity for SOR, basic cobalt carbonate on the surface of needle-like nanorods can -1 NaOH and 1 mol L -1 The activation process is accompanied by the formation of cobalt sulfide-coated cobalt hydroxide carbonate needle-like nanorods (Co-S / NF), which serve as effective active sites for SOR. This transformation can first be reflected in the color of the electrode, which changes from pink (Co-C / NF) to black. The XRD pattern of Co-S / NF ( Figure 1 Lower left inset) shows that Co(CO3) 0.5 The characteristic diffraction peaks of (OH)·0.11H2O became weaker, and some peaks even disappeared compared with Co-C / . These results indicate that part of Co(CO3) 0.5 (OH)·0.11H2O is converted into amorphous cobalt-based sulfides during the SOR process.

[0047] Figure 2 c is the SEM image of Co-S / NF, which shows that the surface of the needle-like nanorod array structure becomes rough and the tops of some needle-like nanorods adhere together to form a stable structure, which is different from the initial smooth surface and relatively independent state ( Figure 2 a). Figure 2 The TEM image of Co-S / NF in d further confirms the formation of rough needle-like nanorods and the amorphous structure covered on the surface. Although the long-range ordered lattice inside the nanorods still belongs to Co(CO3) 0.5 The (020) lattice plane of (OH)·0.11H2O, but the surface of the needle-shaped nanorods is covered by a Co-based compound layer, and its lattice is not obvious. The exposed crystal plane is from Co(CO3) 0.5 The (020) lattice plane of (OH)·0.11H2O transforms into an amorphous cobalt-based sulfide. These results confirm the high-position crystalline surface Co(CO3) 0.5 (OH)·0.11H2O can be converted into highly amorphous cobalt-based sulfides during the SOR process. According to the results of XRD and SEM tests, due to diffusion and electrochemical limitations, Co(CO3) 0.5 (OH)·0.11H2O was not completely converted into amorphous cobalt-based sulfide. In-situ self-reconstruction enables Co-S / NF to obtain a novel and stable nanointerface structure with abundant diffusion paths and improved mechanical strength. In the Co2p XPS spectrum of Co-S / NF ( Figure 2 e), Co2p 1 / 2 XPS at 797.0 (Co 2+ ) and 793.8eV(Co 3+ ) belong to Co 2+ and Co 3+ , and the corresponding Co2p 3 / 2 At 781.4 (Co 2+ ) and 779.4eV(Co 3+ ) were observed to have two XPS peaks. Figure 2 f, the XPS of S is at 161.9 eV (2p 3 / 2 ) and 163.5eV(2p 1 / 2 ) is attributed to S-Co, while the peaks at 168.4 and 169.7 eV indicate the presence of SO bonds. Based on the above results, the activation process of Co-S / NF is accompanied by the surface Co(CO3) 0.5 The decomposition of (OH)·0.11H2O and the formation of Co9S8 with a high degree of amorphization. The low crystallinity of Co9S8 formed in situ on the surface will increase the electrochemically active surface area (ECSA), which is further demonstrated by the double layer dissolution experiment. dl The ECSA of the electrode was calculated. After activation, the ECSA of the electrode per unit macroscopic area increased from 29.75 cm -2 Increase to 47.00cm -2, which is conducive to the full contact between the catalyst and the electrolyte. Therefore, Co-S / NF will show effective electrochemical performance.

[0048] Since Co-C / NF will eventually transform into Co-S / NF during long-term testing, the first linear sweep voltammetry (LSV) curve of the SOR based on Co-C / NF was tested and used for comparison. Figure 3 As shown in a, the catalytic activities of both NF and pristine Co-C / NF electrodes for SOR are relatively low. In contrast, the Co-S / NF electrode exhibits efficient SOR catalytic activity, requiring only a low potential of 0.264 V vs. RHE to reach 10 mA cm -2 The current density is significantly lower than that of Co-C / NF (0.431 V) and NF (0.527 V) as well as the previously reported catalysts ( Figure 3 b). Meanwhile, the advantage of Co-S / NF becomes more obvious with the increase of current density. The outstanding catalytic activity of Co-S / NF, especially at high current density, is beneficial for practical applications. Tafel plots were also collected to study the SOR process ( Figure 3 c). Co-S / NF shows about 50.0mV dec -1 The low Tafel slope is smaller than the initial Co-C / NF (226.2mV dec -1 ) and NF(174.4mV dec -1 ). Compared with Co-C / NF and NF, the smaller Tafel slope indicates that the Co-S / NF electrode can obtain a larger current density increment with the increase of applied potential. Co-S / NF also exhibits a smaller charge transfer resistance (R ct ), which indicates that Co-S / NF has efficient charge transfer in the catalytic process. In addition, the smaller R ct and Tafel slope fully demonstrate the fast kinetics of SOR catalyzed by Co-S / NF. The rich hierarchical array structure and highly amorphous surface of the Co-S / NF electrode promote the improvement of ECSA, which not only makes the Co-S / NF electrode have abundant active sites, but also facilitates the full contact between the catalyst surface and the electrolyte. In addition, the contact angle of water droplets on Co-S / NF (43°) is smaller than that of Co-C / NF (53°) and NF (120.05°). This result indicates that the in situ self-reconstruction of the catalytic surface can promote the full exposure of the electrode to the electrolyte and enhance the mass transfer during the catalytic reaction. Therefore, the Co-S / NF electrode shows strong catalytic activity for SOR.

[0049] The polarization current density normalized to the geometric area (GA) can effectively show the overall catalytic performance of the catalytic electrode. Because the presence of microscopic morphology is not conducive to the evaluation of intrinsic activity. ECSA is a more accurate indicator for evaluating the actual exposed area of ​​the catalytic electrode in the electrolyte. Therefore, the current density normalized to ECSA may more reasonably reveal the intrinsic activity. After normalization to ECSA ( Figure 3 d and 3e), the performance of Co-S / NF electrode is still better than the best SOR catalytic activity and the lowest Tafel slope compared with Co-C / NF and NF electrodes. The larger normalized current density and smaller Tafel slope prove that the intrinsic activity of each active site in Co-S / NF is higher than that of Co-C / NF and NF electrodes. The in-situ formed highly amorphous cobalt-based sulfides have abundant defects and unsaturated sites, which can promote the adsorption of reactants and intermediates on the active sites. Therefore, Co-S / NF shows high intrinsic activity for SOR. These results fully demonstrate that the in-situ sulfidation process significantly increases the number of active sites and enhances the intrinsic catalytic activity of SOR, thereby greatly improving the overall catalytic activity. In addition to activity, stability is also a key criterion for evaluating catalysts. According to the constant voltage test at 0.62V vs.RHE, the current density of Co-S / NF after activation is stable during the long test period (30 hours, Figure 3 f) shows little voltage fluctuation, which indicates the robust SOR catalytic stability of Co-S / NF.

[0050] To confirm the advantages of SOR, Figure 4 The polarization curves of OER and SOR catalyzed by Co-S / NF electrode are compared in a. Due to the slow kinetics and high theoretical potential of OER, the Co-S / NF electrode requires ultra-high potentials of 1.587 V and 1.660 V to reach 10 and 100 mA cm, respectively, in 1 M NaOH. -2 The current density ( Figure 4 b). However, when Na2S was introduced into the alkaline electrolyte, the potential to obtain the same current density decreased by 4.5 and 6.1 times, respectively. Such a significant reduction in the anode potential is undoubtedly conducive to reducing energy consumption and improving the energy efficiency of the catalytic reaction. In order to clarify the reaction mechanism of SOR, the changes in the electrolyte were monitored during the electrolysis. As the electrolysis progressed, the color of the anolyte gradually changed from colorless to light yellow and then to dark yellow ( Figure 4 c), which indicates the continuous generation of polysulfides. Figure 4 The results were further examined by UV-visible (UV-vis) spectroscopy in c. The peak at about 300 nm is attributed to polysulfide (S2 2- ) is formed, and its intensity increases with the increase of reaction time. As the prepared sulfur combines with the sulfur ions in the electrolyte to form polysulfide (HS - →Sn 2- ([S n-1 (0) S (2-) 2- ), where \(1 < n\leq8\), the corresponding ultraviolet peak intensity continuously increases. Meanwhile, by adding an acid to the polysulfide-rich electrolyte, the yellow powder can be effectively collected. Figure 4 XRD analysis in d further indicates that the powder is α-S (PDF#08-0247). The efficient Co-S / NF catalytic electrode enhances the adsorption of S 2- , promotes the formation of polysulfide intermediates and the further chain growth of the high solubility of polysulfides in the electrolyte. This process also effectively avoids sulfur precipitation covering the active sites and ensures strong SOR catalytic activity and stability ( Figure 4 d).

[0051] Based on a three-electrode test system ( Figure 5 a), the potential difference between SOR and HER is significantly lower than that between OER and HER, which is positively correlated with the results of the Pourbaix diagram. As shown in Figure 5 b, the theoretical potential of SOR is lower than that of HER, which results in a low potential difference of 0.35 V (\(\Delta V\) + +\(S\) 2- =\(H_2 + S\)) for the overall coupling reaction in an alkaline environment (\(pH = 14\)) ( S-H =\(E\) SOR -\(E\) HER ). However, both HER and SOR are multi-electron transfer processes with a low kinetic process. It is difficult for the coupling reaction to occur at the theoretical voltage, which has been confirmed by the actual \(\Delta V\) S-H (at a current density of about 100 mA cm -2 ) of 0.482 V. Even so, compared with the overall water splitting reaction (OWSR, \(\Delta V\) O-H = 1.776 V at a current density of 100 mA cm -2 ), the power consumption of this full coupling reaction still has great advantages. The ideal coupling between HER and SOR and the high electrocatalytic performance of Co-S / NF encourage us to study electrocatalytic hydrogen production with lower energy consumption. Therefore, the favorable electrolytes for HER and SOR should be adjusted accordingly.

[0052] Example 3 established an asymmetric acid-base coupling electrolytic cell with 0.5 M \(H_2SO_4\) as the cathode solution (\(Pt-C / CP\) as the catalytic electrode) and 1.0 M \(NaOH\) and 1.0 M \(Na_2S\) as the anode solution (\(Co-S / NF\) as the catalytic electrode). Different from the symmetric alkaline electrolytic cell, in the asymmetric acid-base coupling system, \(S\) 2- will be oxidized in the alkaline electrolyte, while \(H\)​+ In acidic electrolyte, it will be reduced to H2. Figure 5 b, Pourbaix diagram shows that the theoretical potential difference between SOR (pH = 14) and HER (pH = 0) is around -0.48 V, which is significantly better than the symmetrically coupled system (0.35 V, pH = 14). The additional electromotive force of -0.83 V (-0.480-0.350 V) comes from the electrochemical neutralization energy (the considerable voltage comes from the pH gradient between the anode and cathode chambers (0.0591×ΔpH)). It should be noted that this ultra-low theoretical potential can effectively overcome the kinetic and thermodynamic barriers of the reaction itself, making it possible for the asymmetric coupled system to produce hydrogen through HER while outputting electricity. The experimental results based on the three-electrode test system further demonstrated this possibility. At 100 mA cm -2 ( Figure 5 The actual potential difference at the current density of c) is -0.398V, which is less than 0V.

[0053] In order to further verify the practical application of Co-S / NF in electrochemically assisted hydrogen and sulfur production, a dual-electrode system based on different coupled electrolytes was established in Example 4. First, a symmetric alkaline electrolyzer using 1.0M NaOH as the cathode electrolyte (Pt-C / CP as the catalytic electrode) and 1.0M NaOH and 1.0M Na2S as the anode electrolyte (Co-S / NF as the catalytic electrode) was demonstrated. The anode chamber and the cathode chamber are separated by a cation exchange membrane. The electrolyzer has the dual functions of energy-saving hydrogen production and simultaneous degradation of sulfide ions to produce sulfur (HER+SOR). Figure 5 c shows that this overall coupling reaction only requires an ultra-low applied potential of 0.424 V to reach 100 mA cm -2 The current density is significantly lower than that of OWSR (1.822 V). The corresponding energy consumption is reduced to 23.3%. Note that the asymmetric coupled system based on SOR only needs a low battery voltage of -0.381 V to achieve 100 mA cm -2 The current density ( Figure 5 d), which indicates that the system can produce H2 and S8 while outputting power. According to the voltage-current curve and power density, this asymmetric-symmetrical coupling system can obtain 50 mW cm -2 Although the asymmetric coupling system of OWSR also shows a lower potential to obtain the same current density compared with the symmetric coupling system of OWSR, the advantages of the asymmetric coupling system based on SOR are still prominent. -2At a current density of 1.3 Å, the energy consumption of the asymmetric coupled system based on the asymmetric acid (HER of Pt-C / CP)-base (SOR of Co-S / NF) coupled electrolyzer is much better than that of the asymmetric coupled system based on OWSR and the symmetric base coupled system based on SOR ( Figure 5 e). When at 100mAcm -2 When 1Kg H2 is produced at a current density of , the asymmetric coupling system based on SOR can save 35.943KW·h and 21.401KW·h of electricity respectively compared with the asymmetric coupling system based on OWSR and the symmetric alkali coupling system based on SOR.

[0054] In addition, the HER of the asymmetric coupled system based on SOR is 100 mA cm -2 The Faradaic efficiency of the current density was evaluated according to Figure 5 f right figure, the actual hydrogen production is in good agreement with the theoretical value, and the Faraday efficiency of hydrogen production is 97%-98%. The long-term stability of the asymmetric coupling system based on SOR was further tested. Figure 5 As shown in Figure 5g, although the electrolytic cell voltage increased during continuous operation, it still returned to a lower value after replacing the electrolyte, which confirms the high stability of this unique coupling system.

[0055] Example 5

[0056] Preparation of Co-C / NF:

[0057] like Figure 1 As shown, nickel foam was first treated with 1 mol L -1 HCl was ultrasonically treated for 15 min, and then washed several times with distilled water and ethanol to remove surface impurities; Co(NO)3 (5 mmol) and CO·(NH)2 (25 mmol) were dissolved in 40 mL of deionized water under stirring. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave (50 ml), and the NF was vertically immersed in the solution and heated at 140 °C for 6 h. After naturally cooling to room temperature, the electrode was washed several times with deionized water and dried in an oven at 70 °C for 6 h to obtain nickel foam loaded with basic cobalt carbonate (Co-C / NF), with a mass loading of basic cobalt carbonate of approximately 2.3 mg cm -2 .

[0058] Preparation of Co-S / NF:

[0059] In the three-electrode system, the Co-C / NF electrode and graphite rod prepared in Example 1 were used as the working electrode and counter electrode, respectively, and the Ag / AgCl (saturated potassium chloride) electrode was used as the reference electrode. -1 NaOH and 1 mol L -1The electrode was treated in Na2S electrolyte at a constant potential of 0.35 V vs. RHE for 12 hours, and the electrode obtained after electrochemical activation was repeatedly washed with deionized water and dried to obtain a Co-S / NF electrode.

[0060] Example 6

[0061] Preparation of Co-C / NF:

[0062] like Figure 1 As shown, the nickel foam was first treated with 1 molL -1 HCl was ultrasonically treated for 15 min, and then washed several times with distilled water and ethanol to remove surface impurities; Co(NO)3 (5 mmol) and CO·(NH)2 (25 mmol) were dissolved in 40 mL of deionized water under stirring. The solution was then transferred to a polytetrafluoroethylene-lined stainless steel autoclave (50 ml), and the NF was vertically immersed in the solution and heated at 100 °C for 8 h. After naturally cooling to room temperature, the electrode was washed several times with deionized water and dried in an oven at 70 °C for 6 h to obtain nickel foam loaded with basic cobalt carbonate (Co-C / NF), with a mass loading of basic cobalt carbonate of approximately 2.3 mg cm -2 .

[0063] Preparation of Co-S / NF:

[0064] In the three-electrode system, the Co-C / NF electrode and graphite rod prepared in Example 1 were used as the working electrode and counter electrode, respectively, and the Ag / AgCl (saturated potassium chloride) electrode was used as the reference electrode. -1 NaOH and 1 molL -1 The electrode was treated in a Na2S electrolyte at a constant potential of 0.35 V vs. RHE for 12 hours, and the electrode obtained after electrochemical activation was repeatedly washed with deionized water and dried to obtain a Co-S / NF electrode.

[0065] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An amorphous cobalt sulfide electrode, characterized in that: The amorphous cobalt sulfide electrode is prepared by the following method: (1) Dissolving Co(NO)3 and CO·(NH)2 in water, immersing nickel foam NF in the solution, and performing a hydrothermal reaction to obtain nickel foam Co-C / NF loaded with basic cobalt carbonate; (2) A three-electrode system was constructed using nickel foam Co-C / NF loaded with basic cobalt carbonate as the working electrode, and a constant potential activation treatment was performed in an electrolyte solution including NaOH and Na2S to obtain an amorphous cobalt sulfide Co-S / NF electrode after electrochemical activation; The concentration of Co(NO)3 in step (1) is 0.125 mol L -1 The concentration of CO·(NH)2 is 0.625 mol L -1 ; The hydrothermal reaction temperature is 100-140°C, and the hydrothermal reaction time is 6-10h; The concentration of NaOH in step (2) is 1 mol L -1 , the concentration of Na2S is 1 mol L -1 ; The counter electrode of the three-electrode system is a graphite electrode, and the reference electrode is a Hg / HgO electrode or an Ag / AgCl saturated potassium chloride filling solution electrode; The potential of the constant potential activation treatment is 0.35 V vs. RHE, and the activation treatment time is 10-12 h.

2. An application of the amorphous cobalt sulfide electrode according to claim 1 in sulfide ion oxidation-assisted hydrogen production, characterized in that: An asymmetric acid-base coupling electrolytic cell is established by using H2SO4 solution as cathode electrolyte, NaOH and Na2S electrolyte solution as anode electrolyte, using a cation exchange membrane to separate the anode liquid and the cathode liquid, and providing an anode catalytic electrode and a cathode catalytic electrode in the anode electrolyte and the cathode electrolyte, respectively, wherein the anode catalytic electrode uses the amorphous cobalt sulfide electrode described in claim 1; The cathode catalytic electrode uses a platinum carbon electrode; The concentration of H2SO4 is 0.5 mol L -1 The concentration of NaOH electrolyte solution is 1 mol L -1 The concentration of Na2S electrolyte solution is 1 mol L -1 ; The cation exchange membrane is a polyethylene cation exchange membrane.